Effect of four traditional Chinese medicine monomers on mechanical barrier damage and inflammation response of IPEC-J2 cells caused by soybean 7S globulin - Deng, Youtian; Wu, Xiaoli; Wan, Yingying; Deng, Junliang; Deng, Huidan (Frontiers in Veterinary Science, 2025)
IntroductionThe soybean 7S globulin is a major allergen responsible for diarrhea in weaned piglets, leading to significant economic loss in the pig breeding industry. Therefore, there is an urgent need to find effective and safe therapeutic agents to prevent and treat diarrhea caused by soybean 7S globulin. Given the global trend toward “antibiotic alternatives,” traditional Chinese medicines (TCMs) offer a promising approach for the prevention and control of animal diseases.MethodsIn this study, four TCM monomers (curcumin, eleutheroside E, saponin B4, and forsythia A) were evaluated for their protective and therapeutic effects on intestinal epithelial cells (IPEC-J2) damaged by soybean 7S globulin. The CCK8 assay, western blot assay, Elisa assay, and PCR assay were used in this study.ResultsThe results demonstrated that curcumin at concentrations of 0.02, 0.04, and 0.08 μg/mL, eleutheroside E at 25, and 50 μg/mL, saponin B4 at 12.5, 25, and 50 μg/mL, and forsythia A at 20, and 40 μg/mL had significant ameliorative effects on cell viability, permeability, and integrity. Furthermore, the TCM monomers alleviated the inflammatory response, reduced the disruption of tight junctions, and improved the cellular mechanical barrier. These protective effects were likely mediated through the inhibition of the Rho/ROCK signaling pathway, characterized by down regulation of RhoA, ROCK1, ROCK2, and MLKC expression.DiscussionThese findings suggest that the four TCM monomers have the potential to treat diarrhea of weaned piglets caused by soybean protein.